El error de preguntar por la naturaleza de los problemas filosóficos. Crónica de una denuncia wittgensteiniana - Ariso, José María (Logos. Anales del Seminario de Metafísica, 2003)
Many authors have tried to offer a definition of Wittgenstein’s conception of philosophical problems. In this paper my aim is to show that essentialist tendency is just the opposite of Wittgenstein’s attitude, an attitude based on paying attention to the clarification of misunderstandings concerning the use of words: the term ‘problem’ invites us to think on the corresponding ‘solution’, but far from offering solutions or explanations, Wittgenstein wanted to show a philosophical modus operandi comparable to the task of untying knots.